Socioeconomic inequalities in risk of small for gestational age birth in primiparous and multiparous women: analysis of a population-based cohort in the south of England. (November 2018) - Wilding, Sam; Ziauddeen, Nida; Roderick, Paul; Alwan, Nisreen A
Abstract: Background: Small for gestational age (SGA) babies have increased risk of later morbidity. Birth of the first child is a life-changing event that affects biology, behaviour, and social circumstances. We aimed to examine socioeconomic inequalities in SGA risk, and explore potential mediators and effect modification by parity. Methods: We used the first antenatal care record for each mother aged 18 years or older presenting before 24 weeks' gestation with a live singleton birth at University Hospital Southampton, UK (2004–16). Logistic regression models estimated SGA risk by maternal educational qualification, employment, partner's employment status, and lone motherhood, recorded at the first antenatal appointment, adjusting for maternal age, ethnicity, blood pressure, baby's sex, and mediators (maternal body-mass index and smoking status). Lone mothers were those who provided information on their employment status, but not on their partner's. We tested for effect modification by parity, and then stratified by it if there was evidence of interaction. We used 5% statistical significance level for the interaction analysis and 1% for all other analyses. Findings: There were 44 168 births (28 470 primiparous and 15 698 multiparous women). The association with SGA was modified by parity status for maternal education status and employment (interaction p values 0·03 and 0·02, respectively). In fully-adjusted stratified models, women with no university degree had higher SGA risk than did those with a degree, with the association being stronger in multiparous mothers (adjusted odds ratio primiparous 1·16, 99% CI 1·04–1·30; multiparous 1·35, 1·08–1·68). Women in unemployment had higher SGA risk than those in employment (primiparous 1·32, 1·17–1·50; multiparous 1·22, 1·03–1·43). Smoking mediated the association between lone motherhood and SGA (1·16, 1·00–1·34). Interpretation: Inequalities in SGA risk using all socioeconomic indicators were evident, with a stronger association with maternal educational attainment in multiparous women. Maternal smoking is a possible explanation for the association for lone motherhood. Socioeconomic variables were self-reported at one point during pregnancy, which is a limitation. Excluding teenage pregnancies and those booked after 24 weeks' gestation may have diluted the socioeconomic differences in SGA risk. SGA preventive interventions should target the socially disadvantaged including postpartum smoking cessation. Funding: Supported by anAcademy of Medical Sciences and Wellcome Trust grant to NAA (grant no AMS_HOP001\1060 ) and the National Institute for Health Research through the NIHR Southampton Biomedical Research Centre. The funders had no role in designing the research or writing the abstract.